Investigating the impact age has on within-over and death bowling performances in international level 50-over cricket - Jamil, M.; Harkness, A.; Mehta, S.; Phatak, A.; Memmert, D.; Beato, M. (Research in Sports Medicine, 2023)
The aims of this investigation were to determine if ageing effects were present in elite international level cricket. Ball-by-ball data were analysed for 96 bowlers in the 50-Over World Cup 2019. Bowlers were categorized into 1 of 3 age groups GROUP 1 (18-24), GROUP 2 (25-31) and GROUP 3 (32+). Ordinal Logistic Regressions (OLR) and Multinomial Logistic Regressions (MLR) were conducted to estimate the relationship between age and bowling performances. OLR Results revealed that younger bowlers were significantly more likely to concede a greater number of runs on the last ball of their overs than their older counterparts (p = 0.001). A separate MLR analysis was conducted for those bowlers entrusted to bowl during the "death" phase of an innings, and results revealed that GROUP 2 bowlers were significantly more likely to take wickets than either GROUP 1 (p = 0.021) or GROUP 3 (p = 0.022) bowlers. The evidence indicates that wicket taking "death bowlers" will likely perform at their peak between the ages of 25-31, which could inform the bowling strategy of team captains. Furthermore, there is evidence to suggest that younger bowlers are not as skilled as their older counterparts at restricting runs conceded.